2017
DOI: 10.1152/ajpcell.00206.2016
|View full text |Cite
|
Sign up to set email alerts
|

FXYD5 (dysadherin) may mediate metastatic progression through regulation of the β-Na+-K+-ATPase subunit in the 4T1 mouse breast cancer model

Abstract: FXYD5 is a Na-K-ATPase regulator, expressed in a variety of normal epithelia. In parallel, it has been found to be associated with several types of cancer and effect lethal outcome by promoting metastasis. However, the molecular mechanism underlying FXYD5 mediated invasion has not yet been identified. In this study, using in vivo 4T1 murine breast cancer model, we found that FXYD5-specific shRNA significantly inhibited lung cancer metastasis, without having a substantial effect on primary tumor growth. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…To date, to the best of our knowledge, no additional partners for interaction have been described for FXYD5, apart from for the Na + /K + -ATPase subunits (14,33). Previous studies have demonstrated that the SMAD7-SMURF2 complex is recruited to the TGF-β receptor complex, where it results in the ubiquitination and degradation of the receptors as well as SMAD7 via the proteasome-mediated signaling pathway (9,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, to the best of our knowledge, no additional partners for interaction have been described for FXYD5, apart from for the Na + /K + -ATPase subunits (14,33). Previous studies have demonstrated that the SMAD7-SMURF2 complex is recruited to the TGF-β receptor complex, where it results in the ubiquitination and degradation of the receptors as well as SMAD7 via the proteasome-mediated signaling pathway (9,34).…”
Section: Discussionmentioning
confidence: 99%
“…FXYD domain-containing ion transport regulator 5 (FXYD5) has been identified as a cancer-associated protein whose expression inhibits E-cadherin and promotes metastasis (11)(12)(13). As a single span type I membrane protein and an auxiliary subunit of the Na + /K + -ATPase, FXYD5 also modulates cellular junctions and adhesion through the regulation of the β-Na + -K + -ATPase subunit (12)(13)(14)(15)(16). Additionally, Nam et al (17) have reported that C-C motif chemokine ligand mediates the pro-metastatic effect of FXYD5 in human breast cancer cells.…”
Section: A Fxyd5/tgf-β/smad Positive Feedback Loop Drives Epithelial-mentioning
confidence: 99%
“… 8 A recent investigation on molecular mechanisms linked to cancer progression in an in vivo breast cancer model pointed to the direct interaction between FXYD5 and its partner Na + /K + -ATPase pump in multiple steps of the tumour spread process, such as epithelial-mesenchymal transition, loss of cell adhesion and gain of motility. 50 In particular, FXYD5-dependent downregulation of the Na + /K + -ATPase pump beta subunit (beta 1 isoform) mediated the metastatic progression of breast cancer in a mouse model 50 while the suppression of the beta-subunit has been linked to the loss of tight junctions that promotes cell motility and cancer metastasis. 36 …”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, FXYD5 was shown to mediate substitution of β1 isoforms to β3 isoforms ( Lubarski-Gotliv et al, 2017 ). The authors found that in mammary gland tumor cells, β3 isoforms were replaced by β1 isoforms after FXYD5 silencing.…”
Section: Introductionmentioning
confidence: 99%